O Turismo e as normas ISO 9000: um caminho para a certificação da qualidade dos produtos e serviços - Yasoshima, José Roberto (Revista Turismo em Análise, 1994)
A new world economic scenery shows the increasement of products and services quality request. While one of the most important activity tourism requires a new position of all turistic organizations in the way of quality and productivity. The total quality system certification is the best way for a world-wide recognition.